Efecto de la resolución espacial de modelos digitales de elevación en la simulación de derrames de hidrocarburos - Daza-Leguizamón, Omar Javier; Vera-López, Enrique; Riaño-Cano, Gladys Alcira (Revista Científica, 2016)
Simulations of hydrocarbon spills on the surface of the land are useful in environmental impact studies and pipeline integrity management. The identification and assessment of impacts caused by these events requires the simulation in geographic information systems software. The input data for these simulations are fluid properties and terrain characteristics. The relief is generally represented by digital elevation models in raster data format of different pixel sizes. In this study, we analyze the effect of the spatial resolution of digital elevation models on the simulation of areas affected by hydrocarbon spills. We propose an algorithm implemented in GRASS GIS free software and then apply it to an area with cartography at different scales. The simulation was performed for a mountainous zone in the central zone of Colombia, assuming a pipeline of 12 inches of diameter. The analysis of the spatial resolution effects required the comparison of the maximum length, area and curvature of the terrain for the affected area. The results show that the affected extension is larger for pixel sizes of 15 and 30 meters. In addition, the loss of detail of the features of the relief for resolutions of 15 and 30 meters can significantly modify both the affected area and the maximum reach and direction of the spill.